Drinking water practices and sanitation in slums of Visakhapatnam, Andhra Pradesh a developing smart city in India - Veesa, Karun Sandeep; Dimmala, Chandra Shekhar; Antipas, Obed John Heber; Mohan, Venkata Raghava; John, Sushil Mathew (International Journal Of Community Medicine And Public Health, 2016)
Background: Inadequate water quality and sanitation contribute to the transmission of faeco- orally transmitted diseases. Methods: This community based cross sectional study assessed drinking water, sanitation and factors associated with reported 2 week recall diarrhea burden among under-five children in slums. 220 households with under-five children were selected across 14 slums of Zone-6, Visakhapatnam by cluster sampling. A WHO drinking water and sanitation questionnaire was used. Hydrogen sulfide (H2S) water quality test was performed at point of source and use. Data subjected to bivariate and multivariate logistic regression analysis. Results: Mean age of mothers and children were 24.4 (SD 3) years and 28.3 (SD 14.5) months. Study finds 33% (20/60) source samples and 34% (75/220) point of use samples were contaminated. Reported diarrhoea episodes was 14% (31/220) (95% CI 9.4 - 18.5%). All public water system samples were contamination free. Higher contamination rates were observed in untreated private water systems. Despite 41.4% (91/220) households using boiling or filtration methods, 26.4% (24/91) of these samples were contaminated. Factors significantly associated with reported diarrhoea were, low SES (OR 2.3, 95% CI 1.0 – 5.5), unsafe defecation practice (OR 2.2, 95% CI 1.0 – 4.9) and age less than 2 years (OR 2.4, 95% CI 1.0 – 5.5). Conclusions: All treated public water supplied by Municipal Corporation was contamination free and use of this supply should be encouraged. Safe child defecation practices and effective household water treatment methods should be promoted in slums.